The Role of Job Satisfaction in Mediating the Influence of Leadership and Work Environment on the Performance of Employees in the General Department of the Regency DPRD Secretariat Raja Ampat - Mambrasar, Dominggas; Indiani, Ni Luh Putu; Surasmi, Ida Ayu (International Journal of Environmental, Sustainability, and Social Science, 2026)
Performance is the result of a person's work in carrying out their main duties, obligations, and functions as an employee with work results in quality and quantity in accordance with the responsibilities given to them. The variables of leadership, work environment, and job satisfaction can play an important role in building good employee performance. Therefore, individual performance and company performance are very important for organizational leaders to design effective strategies in facing the ever-changing dynamics of work. This study aims to analyze the role of job satisfaction in mediating the influence of leadership and work environment on the performance of employees in the General Section of the Raja Ampat Regency DPRD Secretariat. The population of 39 employees was sampled using saturated sampling technique. Data analysis used the SEM-PLS approach. The results showed that leadership has a positive and significant effect on employee performance, while leadership has no significant effect on job satisfaction. The work environment has a positive and significant effect on employee performance. The work environment has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction has been shown to have a significant effect on employee performance and acts as a partial mediator in the relationship between leadership and work environment on performance. The practical implication of this research is that one of the efforts to improve performance is that organizations need to set clear and measurable work targets according to the workload of each employee.